The Role of Political Ideology in Agreement with Prisoner Responsibility for Personal Safety and Well-Being - Hansen, Michael A.; Navarro, John C. (Springer, 2025)
Although the United States leads the world in its imprisonment rate, an investigation of American public attitudes toward the safety and well-being of prisoners has not kept pace. In a survey distributed via Mechanical Turk (MTurk) (n = 979), the authors explore how respondents’ political ideology influences their views on seven specific aspects of prison conditions related to prisoners’ self-defense and responsibility for their safety, including physical and sexual assaults, as well as acceptance of poor prison conditions. Political ideology is a large and significant predictor of opinions on these seven aspects of prisoner safety and wellness. Conservatives are more likely than liberals to agree with statements supporting harsher prison conditions. While political ideological gaps are wide, these gaps narrow on statements regarding the expectations of prisoners to defend themselves from physical and sexual assault. These findings add insight into how ideological attitudes may influence justice-related decisions on prison life and punishment for prisoners.